1739a Migrant workers of the health sector. (24th April 2018) - Bigaignon-Fanchette, J; Mathieu, Laurence; Blomet, Joel
Abstract : Introduction: The severe shortage of health workers in developed and developing countries is a critical issue that must be addressed as an integral part of strengthening health systems. Migration of health-care workers has a long history. Each country facing shortages of health workers needs to identify the underlying reasons for the shortages, determine what motivates health workers to remain in the health sector, and evaluate the incentives required for maintaining a competent and motivated health workforce Objectives: Highlight the situation of health workers in developed countries as well as developing countries, to gain a better understanding of the contributing factors to health worker motivation, dissatisfaction and migration. Methods: Understand the factors leading to migration. Examine global evidence on initiatives to retain a competent and motivated health workforce, whether from North to South and vice versa or East to west and vice versa. The review draws on literature and information gathered through a targeted search of websites and databases regarding migration of health care workers Results: Decision-making factors and responses to financial and non-financial incentives have not been adequately monitored and evaluated. Conclusion: Efforts must be made to build evidence base so that countries can develop appropriate workforce strategies and incentive packages.